(untitled) (Agora for Physical Education and Sport, 2020)
This article presents the ideological position that Dr. César Juarros adopted on the concept of physical education and sport and, in particular, on his problematization of children’s physical education during the first third of the 20th century. The controversy takes place at a critical moment of the rise of Swedish gymnastics and sports institutionalization in Spain. A historical methodology and documentary analysis of primary sources of this author makes it possible to discover his critical thinking, which is considered in Spain as the first academic intervention from the fields of social psychology, psychoanalysis and criminology. As we shall see, a hundred years later, Juarros’ position is not far from certain current critical thinking.